Health Benefits of Dietary Phenolic Compounds and Biogenic Amines - Gomez-Gomez, Hector Alonzo [UNESP]; Borges, Cristine Vanz [UNESP]; Minatel, Igor Otavio [UNESP]; Luvizon, Aline Carbonera; Lima, Giuseppina Pace Pereira [UNESP] (Springer Nature, 2019)
The bioavailability of dietary phytochemicals may be influenced by several factors as food matrix, cultivation conditions, host microbiota, and physiological state. Phenolic compounds and polyamines have been associated with various health benefits. However, their role in human health is dependent on interactions with the gut microbiota and conversion to further bioactive compounds. Dietary compounds have a wide range of effects that are play after the binding and/or interaction between these compounds and other molecules.
Keywords: Beverage; Biogenic amines; Fruit; Gut microbiota; Phenolic compounds; Polyamines; Polyphenols; Vegetable